The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.progsurf.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Doped and codoped silicon nanocrystals: The role of surfaces and interfaces

Abstract: Si nanocrystals have been extensively studied because of their novel properties and their potential applications in electronic, optoelectronic, photovoltaic, thermoelectric and biological devices. These new properties are achieved through the combination of the quantum confinement of carriers and the strong influence of surface chemistry. As in the case of bulk Si the tuning of the electronic, optical and transport properties is related to the possibility of doping, in a controlled way, the nanocrystals. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 249 publications
3
40
0
Order By: Relevance
“…Therefore, the dependence of the HOMO-LUMO gap on the Si-NC diameter is a direct consequence of the QC effect (the NC shape does not have any inuence) and thus the observed PL is directly related to the states localized inside the Si-NCs. 60,[78][79][80] For the OH-terminated Si-NCs, instead, the changes in the HOMO-LUMO gap are strongly dependent on the oxidation degree (see Table 1) at the NC interface. In fact, in these NCs, the Si atoms at the interface have a different number of nearby O atoms.…”
Section: Undoped Isolated and Matrix Embedded Si-ncs With Differing Passivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the dependence of the HOMO-LUMO gap on the Si-NC diameter is a direct consequence of the QC effect (the NC shape does not have any inuence) and thus the observed PL is directly related to the states localized inside the Si-NCs. 60,[78][79][80] For the OH-terminated Si-NCs, instead, the changes in the HOMO-LUMO gap are strongly dependent on the oxidation degree (see Table 1) at the NC interface. In fact, in these NCs, the Si atoms at the interface have a different number of nearby O atoms.…”
Section: Undoped Isolated and Matrix Embedded Si-ncs With Differing Passivationmentioning
confidence: 99%
“…The results obtained revealed that the doped Si nanostructures showed different properties with respect to the doped Si-bulk. [58][59][60] From an experimental point of view, several factors contribute to making the interpretation of the measurements on these systems a difficult task. First of all, independent of the fabrication technique, the degree of reproducibility of a single individual NC is very low.…”
Section: Introductionmentioning
confidence: 99%
“…It can be said that the effective passivation of silicon clusters (not only by hydrogen atoms) and diluting the silicon framework with the other atoms (e.g., germanium) to change their initial characteristics is an actual modern problem (see Refs. [ ]). In the presented study, we restrict ourselves to hydrogen doped silicon clusters Si 18 H 12 and Si 19 H 12 either pure or endohedral.…”
Section: Introductionmentioning
confidence: 99%
“…During the last years, various efforts have been dedicated to the study of microscopic properties of Si, Ge, and, recently, of Si/Ge NCs and NWs. A large number of works have proven that their structural, electronic, optical, and transport properties are influenced by the occurrence of different concomitant effects that are related to the size, shape, morphology, passivation, presence of defects, doping, and composition . By permitting the isolation and quantification of the effects induced by all these parameters on both ground and excited state properties of low dimensional systems and the simulation of both radiative and non‐radiative recombination mechanisms, numerical simulations have been adopted with success to investigate microscopic properties of complex nanostructured systems .…”
Section: Introductionmentioning
confidence: 99%